2014
DOI: 10.3892/br.2014.411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression profiles as a tool to uncover tumor markers of liver cancer progression in a rat model

Abstract: Establishing a transcriptomic profile of human hepatocellular liver cancer (HCC) progression is a complex undertaking. A rat model of HCC was employed to develop a transcriptomic profile. Using three interventions, preneoplastic lesions appeared after 30 days and they progressed to HCC by 9 months. Preneoplastic and cancer lesions were characterized for transcriptomic analysis, and RNA from total liver homogenates was obtained at 1, 7, 11 and 16 days after the initiation treatment. RNA from dissected persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Microarrays have been utilized to detect DEGs and non-coding RNA, such as microRNAs and long non-coding RNA in HCC, and especially in HBV-related HCC. Many DEGs have been identified as prognostic and diagnostic markers for the development of HCC [ 9 11 , 20 23 ]. In routine clinical practice, clinicians use staging systems to design different treatment programs, and the BCLC staging system is the most commonly used system for HCC management [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarrays have been utilized to detect DEGs and non-coding RNA, such as microRNAs and long non-coding RNA in HCC, and especially in HBV-related HCC. Many DEGs have been identified as prognostic and diagnostic markers for the development of HCC [ 9 11 , 20 23 ]. In routine clinical practice, clinicians use staging systems to design different treatment programs, and the BCLC staging system is the most commonly used system for HCC management [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differentially expressed genes (DEGs) and associated molecular abnormalities of HCC, especially HBV-related HCC, have been explored by many different groups [ 9 14 ]. However, to our knowledge, the reported studies mainly focused on the identification of distinct gene expression signatures and their usefulness as molecular markers in the prediction of clinical outcomes such as survival, metastasis, and recurrence in patients with HCC [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a follow-up study of possible candidate early cancer markers identified in our previous microarray study, 5 we selected a group of genes that were overexpressed in cancer and showed very small variations in the age-control group at 9 and 18 months. We performed a gene expression analysis of the following six selected genes: ANXA2, DYNLT1, PFKP, KRT19, PLA2G7, and SNX10.…”
Section: Discussionmentioning
confidence: 99%
“…These genes have been identified as candidates for further studies aiming to uncover cancer markers. 5 Of the identified candidate genes, ANXA2, DYNLT1, PFKP, PLA2G7, KRT19, and SNX10 genes were selected for this study. The validation of these six genes by quantitative real-time polymerase chain reaction (qRT-PCR) demonstrated high fold-changes in their expression in neoplastic lesions and low expression profiles in adjacent tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the deregulation of genes via epigenetic mechanisms, we have previously described profound changes in gene expression during liver carcinogenesis using microarray-based gene expression profiling (GEP) ( Vasquez-Garzon et al, 2015 ), including the significant downregulation of several genes. Because deregulation of gene expression through methylation plays an important role in the carcinogenic process, it is necessary to identify new targets that participate in liver carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%